Microbial Isolates from Vegetable Foreign Bodies Inhaled by Dogs - Sara Flisi; Manuel Dall’Aglio; Costanza Spadini; Clotilde Silvia Cabassi; Fausto Quintavalla (Veterinary Medicine International)
Grass-seed inhalation is a common problem in canine patients, in particular during summer months, migrating in upper and lower respiratory tract. Grass awns can harbor bacteria and fungi, causing grass seeds foreign body-related disease (GSFBD). Aim of this study was to investigate the aerobic microbial flora isolated from grass awns extracted from 41 dogs with GSFBD and the antibiotic susceptibility of the isolated bacterial strains. Fifty-four grass awns were localized with diagnostic imaging tests and removed by endoscopy from respiratory tract. The most frequent localizations were in the left nostril and the right hemithorax. Only one grass awn was extracted from each patient except in 7 that had more than one. Bacteriological and mycological cultures, strains identification, and antibiotic susceptibility tests were performed. One or more bacterial strains were isolated from all grass awns. Fungal strains were isolated only in 4 cases. Staphylococcus sp. was the most frequent isolate in the upper respiratory tract (36.8%), while E. coli (24.4%) was the most frequent isolate in the lower tract. Fluoroquinolones and Doxycycline were the most effective antibiotics, while resistance was observed against Gentamicin (>93%), Cefapirin, and Clindamycin (>80%). These data are relevant in relation to the use of these antibiotics in both animals and humans, for the risk of transmission of antibiotic resistant bacteria or resistance genes.